2022
DOI: 10.1039/d1an02313f
|View full text |Cite
|
Sign up to set email alerts
|

Detection of small-sized DNA fragments in a glassy nanopore by utilization of CRISPR-Cas12a as a converter system

Abstract: The fabrication of nanopore with matched pore size, and the existence of multi interferents make the reproducible detection of small-sized molecules by means of solid-state nanopore still challenging. A useful...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 66 publications
0
22
0
Order By: Relevance
“…61 Very recently, Zhang et al also proposed a Gnanopore sensing platform for detection of small DNA fragments by the combined use of a DNA tetrahedron as a signal sensor and CRISPR-Cas12a as a converter system, with the l1 gene encoding HPV18 (a type of human papillomavirus, belonging to the high-risk group) as the target DNA molecule (concentration range: 0.5−50 nM) for the detection of cervical cancer cases (Figure 5e). 80 The G-nanopore at the tip of the glass capillaries is the only connection between the internal and external electrolyte solution. Under a bias potential, ionic current blockage changes caused by single molecule translocation can be detected in the sensing region.…”
Section: Molecule Detection Of Tumorsmentioning
confidence: 99%
“…61 Very recently, Zhang et al also proposed a Gnanopore sensing platform for detection of small DNA fragments by the combined use of a DNA tetrahedron as a signal sensor and CRISPR-Cas12a as a converter system, with the l1 gene encoding HPV18 (a type of human papillomavirus, belonging to the high-risk group) as the target DNA molecule (concentration range: 0.5−50 nM) for the detection of cervical cancer cases (Figure 5e). 80 The G-nanopore at the tip of the glass capillaries is the only connection between the internal and external electrolyte solution. Under a bias potential, ionic current blockage changes caused by single molecule translocation can be detected in the sensing region.…”
Section: Molecule Detection Of Tumorsmentioning
confidence: 99%
“…Previous studies have shown that if BSA was present in the reaction buffer, the noise level of a glass nanopore would severely deteriorate due to the strong adsorption of BSA on the surface of the glass nanopore. 16,17 Unfortunately, for many kinds of enzyme-involved commercial reaction buffers, such as the commercial Cas12a reaction buffer and PCR reaction buffer applied in this experiment, BSA is an essential component that can help to improve the stability of the enzyme during the reaction. Previous works chose to seek an alternative reaction buffer, carry out extra purification steps or apply BSA-free reactions to design sensing strategies.…”
Section: Optimization Of the Signal Transducermentioning
confidence: 99%
“…15 (2) The widespread presence of protein interferents such as bovine serum albumin (BSA) and recombinant albumin in the commercial reaction buffer of enzyme-involved biochemical reactions that are often used to establish sensing or signal amplification strategies will greatly deteriorate the noise level of glass nanopores, drowning the translocation signals that should be generated by the analyte, leading to an experiment failure. 16,17 Valuable works have been done to overcome these two challenges. For the first challenge, researchers have tried to use signal transducers or amplification methods to increase the size of the analyte, enhancing the interaction between target molecules and the glass nanopore to produce better translocation signals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations